Long-Term Outcome of Adolescent Anorexia Nervosa: Family Treatment Apartments Compared With Child Psychiatric Inpatient Treatment - Wallin, Ulf; Holmer, Riitta (Frontiers in Psychiatry, 2021)
Introduction: The family is rarely involved in treatment when the patient with anorexia nervosa (AN) is hospitalized. Family Treatment Apartment (FTA) represents an intervention that includes the family in the intensive treatment of AN. This study compares the short and long-term outcome of adolescents treated in FTA with those who received in-patient hospital care. In FTA the parents are responsible for providing the meal support while in hospital care, the staff is responsible. Methods: Sixty-eight previous patients admitted during the period 1990 – 2009, participated in a follow-up, 43 from the FTA where the whole family is admitted for treatment and 25 from regular psychiatric in-patient care. The follow-up consisted of a personal meeting with structured interviews, measurement of height and weight and self-rating questionnaires. Result: Readmissions due to weight loss within six months from discharge were less common in the FTA group. At follow-up, 14.2 years after admission, there was no difference in eating disorder pathology between the groups. There were significantly lower scores on general psychiatric pathology, and significantly higher scores on quality of life in the FTA group. Discussion: The treatment in FTA aims to give the family an ability to handle AN when it is most challenging. FTA may thus provide a helpful context for treatment with a basic sense of security along with skills that could contribute to better general mental health at follow-up.